Decolonising the Zimbabwean ordinary level Food Technology and Design curriculum - Thenjiwe Mwase; Tendayi Marovah (Taylor and Francis Group, 2023)
Informed by the critical theory, this paper contributes to debates on decolonising education as an agenda for a heritage-driven curriculum espoused by the current Zimbabwe competence-based curriculum. It focuses on the “O” level Food Technology and Design curriculum, an area that has not been much explored. The paper challenges visible and subtle hegemonic tendencies embedded in the school curriculum, making it difficult for school graduates to identify with their heritage. Using literature review and policy documents’ analysis, it explores the place of indigenous leafy vegetables in the “O” level Food Technology and Design curriculum. Two observations are highlighted. Firstly, there is limited space provided for indigenous leafy vegetables in the “O” level Food Technology and Design curriculum. Secondly, not much has been emphasised on the nutritional value of indigenous leafy vegetables. To this end, we argue that the “O” level Food Technology and Design curriculum needs to be decolonised if more space is to be provided to indigenous leafy vegetables. To achieve this, advocacy and a deliberate shift towards the inclusion of indigenous dishes and particularly indigenous leafy vegetables in the teaching and learning of Food Technology and Design ought to be foregrounded.